Combating child pornography in digital era: is Malaysian law adequate to meet the digital challenge? - Abd. Jalil, Juriah (UPM Press, 2015)
Information Communication Technology (ICT) facilitates abuse and exploitation of children online, especially child pornography. A study conducted by the Internet Watch Foundation showed that ICT is responsible for the mushrooming of child pornography into a fast growing business and there is evidence to show that the victims of this abuse are getting much younger. Realising the severity of the threat, various conventions and conferences have been held to address the issue and discuss the methods in combating the problem. For example, the Cybercrime Convention criminalises all related acts of creating, producing, disseminating and possessing of any child abuse images. Similarly, various initiatives have been adopted to combat commercial and non-commercial sexual exploitation of children, particularly the Optional Protocol on the Sale of Children, Child Prostitution and Child Pornography (OPSC). At the national level, countries such as the UK, US and South Korea have enhanced their laws and legal mechanism to safeguard children against these ICT facilitated crimes in line with the international conventions. Based on a comparative analysis, this paper aims to highlight the threat and how the three countries are addressing the problem and analyses the legal position in Malaysia in addressing and combating the use of ICT to commit crimes against children.